Encourage the participation of the Community in the Sustainable Education Project: Towards Human Resource Empowerment - Leliy Kholida, Leliy; Muliyani, Muliyani; Fitriah, Fitriah (LP3M, Universitas Muhammadiyah Kendari, 2024)
This study aims to identify human resource (HR) empowerment strategies in educational management, focusing on optimizing individual potential to achieve sustainable educational goals. The research employs a case study method with a descriptive qualitative approach, gathering data through observation, interviews, and documentation at the Mujahidin Foundation. The findings reveal that HR empowerment not only requires strengthening individuals but also necessitates close coordination and collaboration among educational elements, including teachers, staff, and management. The implementation of a holistic and integrated empowerment strategy is key to creating an educational system that can endure and evolve with the changing dynamics of modern society. In conclusion, the success of HR empowerment in the context of educational management depends on a comprehensive approach that considers not only individual aspects but also integrates all educational elements to achieve broader and sustainable educational objectives.